10. Isolation and identification of Aeromonas sp in goldfish (Carrasius auratus) from several pet shops in Banda Aceh - Hamny Hamny; Muhammad Zulfan; Mahdi Abrar; Maryulia Dewi; Darmawi Darmawi; Razali Daud; Budianto Panjaitan (Universitas Syiah Kuala, 2019)
The aim of this study was to isolate and identify Aeromonas sp from pet shops in Banda Aceh. A total of 15 goldfish were obtained from 3 pet shop in Banda Aceh and examined at the Laboratory of Microbiology, Faculty of Veterinary Medicine, University of Syiah Kuala in Banda Aceh. Isolation of bacteria obtained from liver, kidneys and spleen were cultured in the media Rimler-Shotts (RS) Medium Base. The bacteria were identified based on morphology of the growing bacteria, Gram stain, IMViC test, and biochemical tests. The results showed that there were no Aeromonas sp in goldfish (Carrasius auratus) from three pet shops in Banda Aceh.